Versatile nitrate-respiring heterotrophs are previously concealed contributors to sulfur cycle - Bo Shao; Yuan-Guo Xie; Long Zhang; Yang Ruan; Bin Liang; Ruochen Zhang; Xijun Xu; Wei Wang; Zhengda Lin; Xuanyuan Pei; Xueting Wang; Lei Zhao; et al. (Nature Communications)
Abstract Heterotrophic denitrifiers play crucial roles in global carbon and nitrogen cycling. However, their inability to oxidize sulfide renders them vulnerable to this toxic molecule, which inhibits the key enzymatic reaction responsible for reducing nitrous oxide (N2O), thereby raising greenhouse gas emissions. Here, we applied microcosm incubations, community-isotope-corrected DNA stable-isotope probing, and metagenomics to characterize a cohort of heterotrophic denitrifiers in estuarine sediments that thrive by coupling sulfur oxidation with denitrification through chemolithoheterotrophic metabolism. Remarkably, ecophysiology experiments from enrichments demonstrate that such heterotrophs expedite denitrification with sulfur acting as alternative electron sources and substantially curtail N2O emissions in both organic-rich and organic-limited environments. Their flexible, non-sulfur-dependent physiology may confer competitive advantages over conventional heterotrophic denitrifiers in detoxifying sulfide, adapting to organic matter fluctuations, and mitigating greenhouse gas emissions. Our study provides insights into the ecological role of heterotrophic denitrifiers in microbial communities with implications for sulfur cycling and climate change.